Polyethyleneimine impregnation on activated carbon: Effects of impregnation amount and molecular number on textural characteristics and metal adsorption capacities - Yin, C.Y.; Aroua, M.K.; Daud, W.M.A.W. (Materials Chemistry and Physics, 2008)
This paper presents findings on polyethyleneimine (PEI) impregnation on palm shell activated carbon (AC) with regards to effects of impregnation amount and types of PEI used on surface characteristics as well as metal ions adsorption capacities of the AC. Fundamental interactions between PEI molecules and metal ions on textural surface (micro- and mesopores) of the AC are elucidated. Three types of low molecular weight PEI distinguished by their molecular numbers, Mn (423, 600 and 1200) are used for the impregnation process. Impregnation at 8.41 wt 423-PEI/AC provides optimum increases for nickel and copper adsorption capacities by factors of 2.6 and 1.5 respectively at 49 reduction of Brunauer-Emmett-Teller (BET) surface area as compared to virgin AC. Only 423-PEI molecules are shown to have considerably filled the micropores of AC whereas the 600- and 1200-PEI molecules are too large (in terms of molecular sizes) to infiltrate the micropores.